Outlaw - Davies, Stephen, 1976- (New York : Clarion Books, 2011)
The teenage children of Britain's ambassador to Burkina Faso are abducted and spend time in the Sahara desert with Yakuuba Sor, who some call a terrorist but others consider a modern-day Robin Hood.
MSBA Nominee 2012-13.
Keywords: Kidnapping -- Juvenile fiction; Survival -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Social problems -- Juvenile fiction; Terrorism -- Juvenile fiction; Burkina Faso -- Juvenile fiction; Sahara -- Juvenile fiction